Improvement on the mechanical properties of maleic anhydride/polylactic acid composites with Pinus sylvestris-char. (March 2023) - Wei, Manqi; Li, Qingbo; Jiang, Tao; Ding, Huaqing; Wu, Xinghui; Zhang, Yanfei; Wang, Xiaofeng
Abstract: To improve the environmental friendliness as well as the thermal and mechanical properties of maleic anhydride (MAH)/polylactic acid (PLA) composites, Pinus sylvestris-char was added to the composites and the effects of surface polarity and addition amount of charcoal on the properties of the composites was investigated systematically. In this study, Pinus sylvestris-char/MAH/PLA composites were prepared by melting and molded by 3D printing. The surface structure of Pinus sylvestris-char, as well as the mechanical properties and thermal behaviors of the composites were characterized. DSC and TGA techniques showed that the addition of Pinus sylvestris-char reduced the crystallinity, glass transition temperature, and melting temperature of PLA, which was mainly due to the hindering effect of the added Pinus sylvestris-char and the catalytic decomposition of PLA by surface potassium elements. The tensile strength (44.50 MPa), bending strength (61.98 MPa), and hardness (83.18 HD) of the composites were substantially increased compared with pure PLA materials. Furthermore, the difference in surface polarity between Pinus sylvestris-char and PLA led to agglomeration of Pinus sylvestris-char in PLA, which inhibited stress transfer in the composite matrix. When 7.5 wt% Pinus sylvestris-char prepared at 550 ℃ was added, the composite material exhibits better comprehensive properties. This work provides rationale support for the preparation and application of advanced 3D printing materials. Graphical Abstract: ga1